فلسفة التربية عند المسلمين أبو حامد الغزالي أنموذجا - غنابزية كلثوم; معمري مريم (University of Eloued جامعة الوادي, 2025)
هدفت الدراسة للتعرف عن مضمون النظرية التربوية عند أبو حامد محمد الغزالي الطوسي النيسابوري الصوفي الشافعي االشعري، فهو احد اعالم عصره، و اشهر علماء المسلمين في القرن الخامس الهجري، و ذلك من خالل تحديدنا لمالح الفلسفة التربوية عند الغزالي، ومبادئ التعليم( اداب التعليم عند المعلم و المتعلم) حيث يرى الغزالي ان التربية عبارة عن أسلوب او مهارة يكتسبها الفرد لتكوين الشخصية السليمة، فيعتبر الغزالي ان الطفل هو الجوهرة التي تحمل المسؤوليات في مراحل عدة، ويعود ذلك الى كيفية بناء شخصية الطفل و العناية به من الجانب الروحي و العقلي و الجسدي ، كما أراد الغزالي من خالل مشروعه التربوي تحديد عدة قواعد واسس يسير عليها هذا الطفل، ولقد لخصها في رسالته ايها الولد التي تشمل عدة نصائح تربوية دينية وكذلك ركز الغزالي على اهمية التربية في المجال االخالقي و السياسي، واعتبر ان السياسة بدون مبادئ تربوية حتما سيكون نظام الحكم فاسد، يعني هذا ان الحاكم يجب ان يكون يتسم بالتربية منذ صغره ،كيف لحاكم ال يحمل اي مبادئ اخلاقية تربوية ان يقوم بتسيير شؤون الدولة ، لذا تعتبر التربية اهم ركيزة في جميع المجالات، و ادركنا ان الغزالي من خلال تربيته الروحية أراد ان ينشى مجتمع اسلامي مفعم بالتطبيق الفعلي الواقعي الذي نص عليه كتاب أهل والسنة النبوية، وهذه التربية التي تقوم بقربان العبد لربه وترك كل ما يقوده الى الهالك و الفساد الذاتي او على مستوى المجتمع ، فوظيفة التربية عند الغزالي هي تقوية الروح حتى تتغلب على شهوات الجسد و تسترد مكانتها وسيطرتها عليه. "The aim of this study is to explore the essence of the educational theory of Abu Hamid Muhammad Al-Ghazali Al-Tusi Al-Nisaburi, the Sufi, Shafi’i, and Ash’ari scholar. He was one of the leading figures of his time and one of the most prominent Muslim scholars of the 5th century AH. This was done by identifying the main features of Al-Ghazali's educational philosophy and the principles of teachi—particularly the ethics of education for both teacher and learner.Al-Ghazali viewed education as a method or skill that an individual acquires to build a sound personality. He considered the child to be like a gem that carries responsibilities through various stages of life. This depends on how the child's personality is formed and how well they are cared for spiritually,intellectually, and physically.Through his educational project, Al-Ghazali sought to define several rules and foundations that a child should follow. He summarized these in his treatise “Ayyuha al-Walad” (O My Son), which contain various religious and educational pieces of advice.Al-Ghazali also emphasized the importance of education in the moral and political fields. He believed that politics without educational principles would inevitably lead to a corrupt system of governance. This means that a ruler should be brought up with proper education and moral values from childhood. How can a ruler with no ethical or educational principles be expected to manage the affairs of a state?Therefore, education is considered the most important foundation in all areas. Through his focus on spiritual education, Al-Ghazali aimed to create an Islamic society that is fully committed to the practical and realistic application of the teachings of the Qur’an and the Sunnah. This form of education draws the servant closer to his Lord and leads him to abandon anything that may cause personal or societal destruction and corruption For Al-Ghazali, the function of education is to strengthen the soul so that it can overcome bodily desires and regain its rightful position and control over the self.
مذكرة ماستر قسم الفلسفة تخصص فلسفة عامة
Keywords: التربية الاسلامية; تربية الطفل; اداب المعلم والمتعلم; التربية والاخلاق; التربية والسياسة; Islamic Education; Child Rearing; Teacher and Student Etiquette; Education and Morality; Education and Politics.